Medical care and first aid: an interassociation consensus framework for organised non-elite sport during the COVID-19 pandemic. Issue 2 (22nd February 2021) - Hodgson, Lisa; Phillips, Gemma; Saggers, Robin Terence; Sharma, Sanjay; Papadakis, Michael; Readhead, Clint; Cowie, Charlotte M; Massey, Andrew; Weiler, Richard; Mathema, Prabhat; Larkin, Jo; Gordon, Jonathan; et al.
Abstract : The cessation of amateur and recreational sport has had significant implications globally, impacting economic, social and health facets of population well-being. As a result, there is pressure to resume sport at all levels. The ongoing prevalence of SARS-CoV-2 and subsequent 'second waves' require urgent best practice guidelines to be developed to return recreational (non-elite) sports as quickly as possible while prioritising the well-being of the participants and support staff. This guidance document describes the need for such advice and the process of collating available evidence. Expert opinion is integrated into this document to provide uniform and pragmatic recommendations, thereby optimising on-field and field-side safety for all involved persons, including coaches, first responders and participants. The nature of SARS-CoV-2 transmission means that the use of some procedures performed during emergency care and resuscitation could potentially be hazardous, necessitating the need for guidance on the use of personal protective equipment, the allocation of predetermined areas to manage potentially infective cases and the governance and audit of the process.